Analysis of the zonal waves of tide generating potential caused by celestial bodies - Petroškevičius, Petras; Popovas, Darius (Geodesy and Cartography, 2012)
The article discusses the impact of celestial bodies on the Earth’s gravity. The impact is described with reference to tide generating potential derived as a spherical function. The paper points to the zonal functions of a long period depending on local latitude and the declination of the celestial body. Permanent deformations of zonal waves dependant on latitude only are examined estimating the impact of Lunar and Solar gravity on the elements of the Earth’s gravity highlighting the impact on the territory of Lithuania. The obtained results can be used for evaluating the impact of celestial bodies in precise geodetic and gravimetric measurements. Article in Lithuanian Dangaus kūnų lemiamo potvynio potencialo zoninių bangų analizė Santrauka. Nagrinėjamas dangaus kūnų poveikis Žemės sunkio laukui. Poveikis aprašomas potvynio potencialu, išreiškiant sferinių funkcijų eilute. Išskiriamos ilgo periodo zoninės bangos, priklausančios nuo vietos platumos ir dangaus kūno deklinacijos. Išnagrinėtos zoninių bangų nuolatinės deformacijos, priklausančios tik nuo platumos. Įvertintas Mėnulio ir Saulės poveikis Žemės sunkio lauko elementams, išskiriant poveikį Lietuvos teritorijoje. Tyrimų rezultatai gali būti panaudoti dangaus kūnų poveikiui įvertinti atliekant tiksliuosius geodezinius ir gravimetrinius matavimus. Reikšminiai žodžiai: dangaus kūnų poveikis, potvynio potencialas, zoninės bangos. First published online: 03 Aug 2019